Current reference pierce oscillator circuit topology for low phase noise MEMS SAW oscillator / Fazli Lut, Norlizawati Kamarudin and Jamilah Karim - Lut, Fazli; Kamarudin, Norlizawati; Karim, Jamilah (UiTM Press, 2018)
This paper presents the design and simulation of a current reference Pierce oscillator circuit topology for microelectromechanical systems (MEMS) based oscillator. The designed amplifier achieves a gain of 33 dB at VDD of 1.2V. The amplifier core was tested with surface-acousticwave (SAW) resonators range from 800MHz to 2.4 GHz to form an oscillator and it shows a phase noise level range of -146 dBc/Hz to -151 dBc/Hz at 100 kHz offset frequency. This satisfies the maximum requirements phase noise of local oscillator (LO) of ultra-high frequency (UHF) for Bluetooth technology and Global System for Mobile Communications (GSM). The device produced a better figure-of-merit (FoM) when compared with other oscillators that were based on CMOS on-chip inductor and capacitor (CMOS LC), film bulk acoustic resonator (FBAR) and lateral-field-excited (LFE) Aluminium Nitride (AIN) contour mode resonators technologies. The oscillator circuit has been simulated using a 0.13µm CL130G CMOS technology process from Silterra (Malaysia) with the oscillator core consuming only 1.07mW DC power.